2024
DOI: 10.1111/jnc.16032
|View full text |Cite
|
Sign up to set email alerts
|

Brain energy metabolism: A roadmap for future research

Caroline D. Rae,
Joseph A. Baur,
Karin Borges
et al.

Abstract: Although we have learned much about how the brain fuels its functions over the last decades, there remains much still to discover in an organ that is so complex. This article lays out major gaps in our knowledge of interrelationships between brain metabolism and brain function, including biochemical, cellular, and subcellular aspects of functional metabolism and its imaging in adult brain, as well as during development, aging, and disease. The focus is on unknowns in metabolism of major brain substrates and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 572 publications
0
9
0
Order By: Relevance
“…Together, our findings suggest that although palmitate increases mitochondria biogenesis, it reduces the efficiency of respiration and exacerbates glycolysis. Using 13 C tracing experiments, we further found that palmitate further increases the rate of pyruvate carboxylation, which is needed for de novo oxaloacetate synthesis (Rae et al ., 2024), and supports the drainage of Krebs cycle intermediates used in biosynthetic pathways during increased cellular proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…Together, our findings suggest that although palmitate increases mitochondria biogenesis, it reduces the efficiency of respiration and exacerbates glycolysis. Using 13 C tracing experiments, we further found that palmitate further increases the rate of pyruvate carboxylation, which is needed for de novo oxaloacetate synthesis (Rae et al ., 2024), and supports the drainage of Krebs cycle intermediates used in biosynthetic pathways during increased cellular proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…Glutamate, aspartate, and lactate are central to brain metabolism, playing crucial roles in supporting physiological functions critical for cognitive processes 37,38,61 . These metabolites, interconnected through the tricarboxylic acid (TCA) cycle and glycolysis (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proton ( 1 H)-MRS enables the quantification of several brain metabolites, such as glutamate, lactate, aspartate, N-acetylaspartate (NAA), creatine, and others. These metabolites play crucial roles in neuronal health, energy metabolism, and cellular signaling, all key for neural function and behavior production [36][37][38] . Understanding whether the concentrations of these metabolites in key brain regions are related to effort-based motivated processes can provide invaluable insights into the neurometabolic foundations of these cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, peripheral administration’s effects on subjective fatigue and effort perception [90, 91] or in effort performance and locomotor activity [70, 71] are not always consistent, indicating a need for further well-powered interventive studies to clarify lactate’s role in effort-based decision-making and fatigue. An interaction with other plasma metabolites may be crucial for lactate’s signaling effect [92, 93], as high lactate levels combined with ATP and H + in muscle can induce sensations of peripheral fatigue and pain, whereas none of these metabolites alone produce such effects [91].…”
Section: Discussionmentioning
confidence: 99%